A Cross-Sectional Study Demonstrating Increased Serum Amyloid A Related Inflammation in High-Density Lipoproteins from Subjects with Type 1 Diabetes Mellitus and How This Association Was Augmented by Poor Glycaemic Control. (18th October 2015) - McEneny, Jane; Daniels, Jane-Ann; McGowan, Anne; Gunness, Anjuli; Moore, Kevin; Stevenson, Michael; Young, Ian S.; Gibney, James
Abstract : Inflammatory atherosclerosis is increased in subjects with type 1 diabetes mellitus (T1DM). Normally high-density lipoproteins (HDL) protect against atherosclerosis; however, in the presence of serum amyloid-A- (SAA-) related inflammation this property may be reduced. Fasting blood was obtained from fifty subjects with T1DM, together with fifty age, gender and BMI matched control subjects. HDL was subfractionated into HDL2 and HDL3 by rapid ultracentrifugation. Serum-hsCRP and serum-, HDL2 -, and HDL3 -SAA were measured by ELISAs. Compared to control subjects, SAA was increased in T1DM subjects, nonsignificantly in serum( P = 0.088 ), and significantly in HDL2 ( P = 0.003 ) and HDL3 ( P = 0.005 ) . When the T1DM group were separated according to mean HbA1c (8.34%), serum-SAA and HDL3 -SAA levels were higher in the T1DM subjects with HbA1c ≥ 8.34%, compared to when HbA1c was <8.34%( P < 0.05 ) . Furthermore, regression analysis illustrated, that for every 1%-unit increase in HbA1c, SAA increased by 20% and 23% in HDL2 and HDL3, respectively, independent of BMI. HsCRP did not differ between groups( P > 0.05 ) . This cross-sectional study demonstrated increased SAA-related inflammation in subjects with T1DM that was augmented by poor glycaemic control. We suggest that SAA is a useful inflammatory biomarker in T1DM, which may contribute to their increased atherosclerosis risk.